TECHNOLOGY STRESS IN PERIOPERATIVE NURSING: AN ONGOING CONCERN. - Smith, Judith; Palesy, Debra (ORNAC Journal, 2020)
The following discussion will explore the impact of technology on perioperative nursing roles and the development of the phenomenon coined 'technology stress'. We will begin by reviewing the ongoing debate of technical versus caring nursing practices. The impact of advanced technology on perioperative nursing roles is explored, highlighting the development of technology stress. The paper concludes with some recommendations for further research.